2019
DOI: 10.1089/chi.2019.0025
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adiposity and Puberty on Thyroid Function in Children and Adolescents

Abstract: Background: In the context of a worldwide increase in childhood obesity, euthyroid hyperthyrotropinemia has been consistently reported and raises questions about its etiology, its potential metabolic complications, and its management. In this study we analyze the thyroid function with respect to BMI, pubertal status, and sex in children with obesity and discuss our results on an integrative context with the existent data from the literature.Methods: In this case-control study, we compared 389 children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The finding of significantly more conduct problems in children and adolescents with higher BMI-SDS is more surprising, as previous studies did not find such association [ 23 , 24 ]. Various studies have documented an altered hormone balance in children and adolescents with obesity [ 48 , 49 ]. Since various hormones can also influence behavior, this could be a reason for more frequent conduct problems in children and adolescents with higher BMI-SDS.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of significantly more conduct problems in children and adolescents with higher BMI-SDS is more surprising, as previous studies did not find such association [ 23 , 24 ]. Various studies have documented an altered hormone balance in children and adolescents with obesity [ 48 , 49 ]. Since various hormones can also influence behavior, this could be a reason for more frequent conduct problems in children and adolescents with higher BMI-SDS.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from studies that show the reverse, there are other studies that show a positive association between blood TSH levels and BMI. 5 , 31 On the other hand, Giannakopoulos et al 32 indicated that whereas BMI and TSH had a positive relationship in prepubertal girls and boys with obesity, this correlation is not maintained after the onset of puberty. They suggested that pubertal levels of estradiol could be responsible for this dissociation between BMI and TSH by obtaining the leptin-mediated increase in TSH.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies in children and adolescents have found an association between elevated TSH levels or SH and obesity (12)(13)(14)(15)(16)(17). An association has also been demonstrated between SH and cardiometabolic risk factors (CMRF), such as hypercholesterolemia (18,19), carotid intima thickness (19) and glucose dysmetabolism (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%